Trends in wildlife intake at a rehabilitation centre in Central Alberta: a retrospective analysis of birds, mammals and herptiles, 1990-2012 - Doell, Dawn; Locky, David (My University, 2016)
Using patient data from the Wildlife Rehabilitation Society of Edmonton, we assessed reasons for admission, overall success of rehabilitation, and compared temporal trends with human population growth in the region. Over the survey period 13,375 individuals from 271 species were admitted. These included 11,637 birds (87%), 1,727 mammals (13%), and 11 herptiles (<0.1%). Outcome data were not reliably collected from 1990 through 2007 so it is not possible to provide a valid rate of the rehabilitated animal release for thoseyears. However, starting in 2008 outcome data was collected for the majority of animals with the average release rate of 45.7% from 2008 through 2012. There was a strong relationship between Edmonton’s population growth and the annual intake of wildlife (R² = 0.84, F = 104.6, P = 0.001). This study provides an overview of wildlife intake trends from 1990 through 2012 and is the first known published retrospective of wildlife intake in Alberta.
Keywords: wildlife rehabilitation; raptors; mammals; birds; reptiles; amphibians; Edmonton